OLIGOMERIZATION IN AS(III) SULFIDE SOLUTIONS: THEORETICAL CONSTRAINTS AND SPECTROSCOPIC EVIDENCE - Helz G.R.; Tossell J.A.; Charnock J.M.; Pattrick R.A.D.; Vaughan D.J.; Garner C.D. (My University, 1995)
Bond distances, vibrational frequencies, gas-phase energetics, and proton affinities for various thioarsenite molecules and ions are predicted from molecular orbital theory and used to interpret EXAFS and Raman spectra of dissolved thioarsenites in undersaturated, alkaline 1 M NaHS solutions. From MO predictions, Raman peaks at 325 and 412 cm-1 are assigned to AsS(SH)-2 and a peak at 382 cm-1 to AsS2(SH)2-. At alkaline pH, As-S distances in dissolved thioarsenites are 2.21-2.23 a and no statistically significant As-As interactions are recorded, consistent with predominance of the monomers, AsS(SH)-2 and AsS2(SH)2-. Estimated proton affinities suggest that thioarsenites with a negative charge greater than 2 are unstable in water. In seeming contradiction to this spectroscopic evidence, a new analysis of published solubility studies reinforces previous inferences that the trimer, As3S4(SH)-2, is the predominant thioarsenite in systems saturated with As2S3. Previously proposed dimeric species of the form, HxAs2Sx-24, are rejected based on predicted thermodynamic properties. Dimer plus tetramer combinations also are rejected. Estimated free energies for AsS(OH)(SH)- and AsS(SH)-2 are presented. We reconcile the spectroscopic and solubility evidence by showing that in undersaturated solutions monomers can become thermodynamically favored over oligomers. This pattern should be looked for in other sulfide systems as well. Sulfidic natural waters are in many cases undersaturated with respect to As2S3 phases, so monomeric thioarsenites could be more important in nature than the trimers that have been characterized in saturated solutions.EXAFS spectra show that amorphous As2S3 resembles orpiment in the first shell around As, but that higher shells are disordered. Disorder may be caused by occasional realgar-like, As-As bonds, consistent with the observation that amorphous As2S3 is slightly S deficient.